Nationwide survey of Leptospira antibodies in dogs in Japan: Results from microscopic agglutination test and enzyme-linked immunosorbent assay - Iwamoto, E.(Yamaguchi Univ. (Japan)); Wada, Y; Fujisaki, Y; Umeki, S; Jones, M.Y; Mizuno, T; Itamoto, K; Maeda, K; Iwata, H; Okuda, M (Journal of Veterinary Medical Science, 2009)
Leptospirosis is an infectious disease caused by Leptospira interrogans sensu lato and is common in both humans and animals. In the present study, serum samples were collected from 801 dogs across all 47 prefectures in Japan, and evaluated with a microscopic agglutination test (MAT), using 5 major L. interrogans serovars (Icterohaemorrhagiae, Canicola, Autumnalis, Hebdomadis, and Australis) as antigens, and an enzyme-linked immunosorbent assay (ELISA) using recombinant OmpL1 protein as the antigen. Across all dogs tested, 217 (27.0%) and 29 (3.6%) were MAT- and ELISA-positive, respectively. However, evidence strongly suggests that MAT also detected antibodies produced by vaccination. Of 243 dogs never inoculated with any canine vaccine, 41 (16.9%) from 23 prefectures were MAT and/or ELISA positive. The most commonly detected serovar was Icterohaemorrhagiae (22 dogs, 19 prefectures). Our results suggest that there are dogs with subclinical Leptospira infection throughout Japan. To the best of our knowledge, the present study is the first nationwide survey of Leptospira infection in dogs, and the findings are relevant not only for clinical veterinary medicine but also for public health.